Mitochondrial Contact Sites in Inflammation-Induced Cardiovascular Disease - Liu, Hao; Liu, Xiao; Zhuang, Haixia; Fan, Hualin; Zhu, Dongxing; Xu, Yiming; He, Pengcheng; Liu, Jinbao; Feng, Du (Frontiers in Cell and Developmental Biology, 2020)
The mitochondrion, the ATP-producing center, is both physically and functionally associated with almost all other organelles in the cell. Mitochondrial-associated membranes (MAMs) are involved in a variety of biological processes, such as lipid exchange, protein transport, mitochondrial fission, mitophagy, and inflammation. Several inflammation-related diseases in the cardiovascular system involve several intracellular events including mitochondrial dysfunction as well as disruption of MAMs. Therefore, an in-depth exploration of the function of MAMs will be of great significance for us to understand the initiation, progression, and clinical complications of cardiovascular disease (CVD). In this review, we summarize the recent advances in our knowledge of MAM regulation and function in CVD-related cells. We discuss the potential roles of MAMs in activating inflammation to influence the development of CVD.